Co-operation of MCL-1 and BCL-XL anti-apoptotic proteins in stromal protection of MM cells from carfilzomib mediated cytotoxicity - Galas-Filipowicz, Daria; Chavda, Selina J.; Gong, Jia-Nan; Huang, David C. S.; Khwaja, Asim; Yong, Kwee (Frontiers in Oncology, 2024)
Introduction BCL-2 family proteins are important for tumour cell survival and drug resistance in multiple myeloma (MM). Although proteasome inhibitors are effective anti-myeloma drugs, some patients are resistant and almost all eventually relapse. We examined the function of BCL-2 family proteins in stromal-mediated resistance to carfilzomib-induced cytotoxicity in MM cells. Methods Co-cultures employing HS5 stromal cells were used to model the interaction with stroma. MM cells were exposed to CFZ in a 1-hour pulse method. The expression of BCL-2 family proteins was assessed by flow cytometry and WB. Pro-survival proteins: MCL-1, BCL-2 and BCL-XL were inhibited using S63845, ABT-199 and A-1331852 respectively. Changes in BIM binding partners were examined by immunoprecipitation and WB. Results CFZ induced dose-dependent cell death of MM cells, primarily mediated by apoptosis. Culture of MM cells on HS-5 stromal cells resulted in reduced cytotoxicity to CFZ in a cell contact-dependent manner, upregulated expression of MCL-1 and increased dependency on BCL-XL. Inhibiting BCL-XL or MCL-1 with BH-3 mimetics abrogated stromal-mediated protection only at high doses, which may not be achievable in vivo. However, combining BH-3 mimetics at sub-therapeutic doses, which alone were without effect, significantly enhanced CFZ-mediated cytotoxicity even in the presence of stroma. Furthermore, MCL-1 inhibition led to enhanced binding between BCL-XL and BIM, while blocking BCL-XL increased MCL-1/BIM complex formation, indicating the cooperative role of these proteins. Conclusion Stromal interactions alter the dependence on BCL-2 family members, providing a rationale for dual inhibition to abrogate the protective effect of stroma and restore sensitivity to CFZ.